USAGE OF PARTS OF BODY IN UZBEK AND ENGLISH IDIOMS - Shamuradova, Naima (Мир исследований, 2021)
Phrases are a special form of language that can take the form of word units and sentences. In recent years, the use of body parts in idioms has involved a lot of research. This article discusses the use of body parts in English and Uzbek language phrases. At the same time, it promotes the development of these languages and the development of communication in them.